Control of Thruster-Assisted, Bipedal Legged Locomotion of the Harpy Robot - Dangol, Pravin; Sihite, Eric; Ramezani, Alireza (Frontiers in Robotics and AI, 2021)
Fast constraint satisfaction, frontal dynamics stabilization, and avoiding fallovers in dynamic, bipedal walkers can be pretty challenging due to underactuation, vulnerability to external perturbations, and high computational complexity that arises when accounting for the system full-dynamics and environmental interactions. In this work, we study the potential roles of thrusters in addressing some of these locomotion challenges in bipedal robotics. We will introduce a thruster-assisted bipedal robot called Harpy. We will capitalize on Harpy's unique design to propose an optimization-free approach to satisfy gait feasibility conditions. In this thruster-assisted legged locomotion, the reference trajectories can be manipulated to fulfill constraints brought on by ground contact and those prescribed for states and inputs. Unintended changes to the trajectories, especially those optimized to produce periodic orbits, can adversely affect gait stability and hybrid invariance. We will show our approach can still guarantee stability and hybrid invariance of the gaits by employing the thrusters in Harpy. We will also show the thrusters can be leveraged to robustify the gaits by dodging fallovers or even jumping over large obstacles.